Impact Of Photoinitiators Types And Concentrations On Color Stability And Degree Of Conversion Of Light Cure Resin Based Composites: A Scoping Review - Arooj, Zartashia; AL-Rawas, Matheel; A. Fatalla, Abdalbseet; Johari, Yanti; Mohamad, Dasmawati; Abdullah, Johari Yap; Husien, Adam (Journal of Neonatal Surgery, 2025)
The study aimed to enumerate synthetic and natural photoinitiators (PIs), and to find out the impact of PIs types and concentrations on color stability and degree of conversion (DC) of light cure resin-based composites. A thorough literature search from the year 1991 to 2022 was done on PubMed, Cochrane Library, Science Direct, Scopus, Wiley Online Library using different descriptors. All the duplicates were removed and a total of 102 full text articles were assessed. A total of 68 full text articles were selected for final assessment and write up. The studies for color stability and DC were arranged in a tabular form and it was noted that the type and concentration of PIs and also when used in combination do affect the color stability and DC of resin composites. Type and concentration of PIs affect the DC and color stability of resin composites. Camphoroquinone is the PI that has been utilized the most up until this point among the several options that have been tried Highlights Understand the range of photoinitiators available to incorporate into chemical structure of composite resin. The type and concentration of photoinitiators play an important role in degree of conversion and color stability of dental composites. Below optimal concentration of photoinitiators, the degree of conversion and hence polymerization are compromised. Above the optimal concentration of photoinitiators, colour stability and biocompatibility concerns may emerge. The combination of camphoroquinone and its co-initiator remains the most frequently utilized photoinitiators.